The Implementation of MUI Fatwa No. 4 of 2003 on Halal Standardization in Processed Chicken Products at Amor Restaurant Purwakarta - Muhammad Azhar Taufikurrrohman; Dian Herdiana; Sumiati Sumiati (IQTISHOD: Jurnal Pemikiran dan Hukum Ekonomi Syariah, 2026)
This study aims to analyze the implementation of MUI Fatwa Number 4 of 2003 concerning Halal Standardization in processed chicken products at the Amor Restaurant in Purwakarta, specifically in the aspects of identifying critical halal ingredients and controlling the production process. This study uses a qualitative approach with a juridical empirical method, through field observations, interviews with business owners, and analysis of documents and normative provisions of the MUI fatwa. The results show that the implementation of halal standardization at the Amor Restaurant is still minimal and informal. The selection of raw materials and the production process is based more on habits, experience, and trust in suppliers without the support of formal verification such as halal certificates, halal SOPs, and material documentation. This condition causes the control of critical halal ingredients, especially in food additives and processed products, not to be managed systematically, thus potentially giving rise to doubts. From the perspective of Islamic jurisprudence (fiqh muamalah), the practice of buying and selling food remains considered legitimate as long as it is not proven to contain haram elements, even though it has not been certified halal. However, from the perspective of Muslim consumer protection and the maqāṣid al-syarī‘ah (obligatory principles of Islamic law), this practice is far from ideal. This research highlights the importance of strengthening education, mentoring, and facilitating halal certification for culinary MSMEs to ensure sustainable halal product assurance.